If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -5)(x + -8) = 0 Reorder the terms: x(-5 + x)(x + -8) = 0 Reorder the terms: x(-5 + x)(-8 + x) = 0 Multiply (-5 + x) * (-8 + x) x(-5(-8 + x) + x(-8 + x)) = 0 x((-8 * -5 + x * -5) + x(-8 + x)) = 0 x((40 + -5x) + x(-8 + x)) = 0 x(40 + -5x + (-8 * x + x * x)) = 0 x(40 + -5x + (-8x + x2)) = 0 Combine like terms: -5x + -8x = -13x x(40 + -13x + x2) = 0 (40 * x + -13x * x + x2 * x) = 0 (40x + -13x2 + x3) = 0 Solving 40x + -13x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(40 + -13x + x2) = 0 Factor a trinomial. x((5 + -1x)(8 + -1x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Subproblem 3
Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8Solution
x = {0, 5, 8}
| v=0.333333ah | | 9x-324=0 | | x^3+7x=5 | | F(4)=5x-1 | | 21.763+X=3.50X+X | | 21.763+X=3.25X+X | | log(x)+log(x+15)=2 | | 10-2x=17-7x | | 4x^2+90x-306=0 | | 1.85X=10+X | | Logx+log(x+15)=2 | | 1.85X=11110+X | | 4(m-13)=8m | | 4n-21=31 | | 2.10X=10+X | | 4(9+a)=6a | | 11=d+15 | | 9c-3(7y-4c)= | | 5=t+7 | | 2a+2b(a+2b)+b= | | 3+q(8+-4q)+-8q=0 | | 3x+(2x^2-6)=6x^3-18x | | 4x-10y=-9 | | (x-12)+(16+2x)=14 | | l(4l-2)=90 | | 10a+-12+-12a+17=0 | | 5x-6y=23 | | 3x^2-20=0 | | 0.625(a-2)=10 | | 131-6x=21x+20 | | 5+4*3-2= | | 11-7x=107-35x |